Regional Aggressive Root Resorption Caused by Neuronal Virus Infection - Inger Kjær; Carsten Strøm; Nils Worsaae (Case Reports in Dentistry)
During orthodontic treatment, root resorption can occur unexplainably. No clear distinction has been made between resorption located within specific regions and resorption occurring generally in the dentition. The purpose is to present cases with idiopathic (of unknown origin) root resorption occurring regionally. Two cases of female patients, 26 and 28 years old, referred with aggressive root resorption were investigated clinically and radiographically. Anamnestic information revealed severe virus diseases during childhood, meningitis in one case and whooping cough in the other. One of the patients was treated with dental implants. Virus spreading along nerve paths is a possible explanation for the unexpected resorptions. In both cases, the resorptions began cervically. The extent of the resorption processes in the dentition followed the virus infected nerve paths and the resorption process stopped when reaching regions that were innervated differently and not infected by virus. In one case, histological examination revealed multinuclear dentinoclasts. The pattern of resorption in the two cases indicates that innervation is a factor, which under normal conditions may protect the root surface against resorption. Therefore, the normal nerve pattern is important for diagnostics and for predicting the course of severe unexpected root resorption.